Acute and Sub-Chronic Toxicity Study of 1-(2, 5-Dihidroxyphenil)-3- Pyridine-2-Il-Propenone In Adult Female Mice - Ika Puspitasari; Ratna Asmah Susidarti; Arief Nurrochmad; Pridiyanto Pridiyanto; Devie Amalia Utami; Pipit Febrian; Thoriq Ziyad (Indonesian Journal of Pharmacy, 2021)
This research aimed to evaluate the toxicity of 1-(2, 5-dihidroxyphenil)-3-pyridine-2-il-propenone (DPP) after 24 hours and 90-day administration in female mice. Acute toxicity test was performed using the OECD 423 method, and DPP was administered once a day at doses of 300, 2000, and 5000 mg/kg body weight (BW). Toxic symptoms were observed after 24 hours of administration, and this continued until the 14th day. The experimental animals were dissected and examined for histological organs on the 15th day. The sub-chronic toxicity test was performed using the OECD 408 method, and DPP at 14, 28, and 56 mg/kg/day was administered for 90 days. Toxic symptoms were observed every day, and the amount of food and water intakes were also measured. Furthermore, statistical analysis was performed, and changes in body weight as well as routine blood checks and biochemistry were observed. At the end of the study, experimental animals were killed and the vital organs' weights were examined before their histological analysis. The results showed that DPP at 300-5000 mg/kg/day and 14-56 mg/kg/day for 90 days did not show any toxic symptom respectively. In the sub-chronic toxicity test, no change was observed in blood and urine biochemical parameters (p≥0.05). However, lymphocytic infiltration in the liver and congested vessel in the kidney occurred after administration at 56 mg/kg / day. The results showed that the acute toxicity of DPP is at category 5 according to Globally Harmonized Classification System and sub-chronic toxicity is at a dose below 56 mg/kg/day.